A phase-field simulation study of irregular grain boundary migration during recrystallization. Issue 1 (July 2015) - Moelans, N; Zhang, Y B; Godfrey, A; Jensen, D Juul
Abstract: We present simulation results based on a phase-field model that describes the migration of recrystallization boundaries into spatially varying deformation energy fields. Energy fields with 2-dimensional variations representing 2 sets of dislocation boundaries lying at equal, but opposite, angles to the moving boundary are considered. The simulations show that the shape and overall migration rate of the recrystallization front is considerably affected by spatial variations in the deformation microstructure. It is seen that, depending on characteristics of the variations in the deformation microstructure, highly asymmetrical protrusions and retrusions can develop on the migrating recrystallization front resulting in a migration velocity considerably larger than that expected from standard recrystallization models. It is also seen that, when the wavelength of the variations in a deformation microstructure along the grain boundary is larger than the wavelength of the variations in the direction of migration, parts of the boundary show a stop-and-go type of migration, resulting in a lower overall migration rate. These simulations thus reproduce and explain many of the typical features observed in recrystallization experiments. They give new insights in the way deformation microstructures can affect the migration behavior of recrystallization boundaries and can lead to a stop-and-go type of migration of the recrystallization boundary even in pure materials.